2021
DOI: 10.1055/s-0040-1722327
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Management in Late Preterm and Term Infants: A Randomized Controlled Trial

Abstract: Objective The study aimed to compare the effects of three different methods of umbilical cord management on hematological parameters in term and late-preterm infants. Study Design A randomized controlled trial comparing intact-umbilical cord milking (I-UCM) with cut-umbilical cord milking (C-UCM) and immediate cord clamping (ICC) in neonates born >35 weeks' gestation. Results A total of 587 infants were evaluated. Of these, 197 were assigned to I-UCM, 190 to C-UCM, and 200 to ICC. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
8
0
3
Order By: Relevance
“…In our study, I-UCM and DCC for term neonates resulted in similar Hb and Hct outcomes, but further controlled trials are required for a full assessment. In our previous study, when comparing I-UCM to C-UCM with immediate cord clamping in neonates delivered >35 weeks' gestation, I-UCM was found to be the better option ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, I-UCM and DCC for term neonates resulted in similar Hb and Hct outcomes, but further controlled trials are required for a full assessment. In our previous study, when comparing I-UCM to C-UCM with immediate cord clamping in neonates delivered >35 weeks' gestation, I-UCM was found to be the better option ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also was found comparisons between the types of milking C-UCM and I-UCM (29,43,57,78) . Other studies performed other types of comparison, such as: UCM x 'non-milking' (34,40) , ICC x DCC x UCM (71) and UCM x DCC x DCC with UCM (25,79) .…”
Section: Resultsmentioning
confidence: 99%
“…A study compare UCM x 'nonmilking', demonstrated benefits in the neurological development of newborns submitted to milking (34,40) . Others that compared ICC x DCC x UCM, finding higher levels of hemoglobin and hematocrit in the last two groups (71) , and greater oxidative stress (13) , higher mortality or major morbidity (56) , lower 5-minute Apgar's score in those submitted to ICC. Also was identified that there were no significant differences between groups for measures of electroencephalogram activity or cerebral near infrared spectroscopy (52) , total oxidant capacity, oxidative stress index, and peroxynitrite measurements (81) .…”
Section: Discussionmentioning
confidence: 99%
“…Whether different techniques of placental transfusion have similar effect on hemoglobin (Hb) level is point of debate in various studies. Kilicdag and Shirk showed no significant differences regarding Hb level between C-UCM and I-UCM, and DCC and I-UCM, respectively [ 18 , 19 ]. Katheria et al showed significant difference in Hb levels between DCC and I-UCM in preterm infants born by C-section, in which infants in DCC group are expected to have lower Hb levels owing to lack of effective uterine contractions in their mothers [ 13 ].…”
Section: Discussionmentioning
confidence: 99%